Ecospirituality : An Introduction - Wheeler, Rachel (Book collections on Project MUSE., 2022)
Ecospirituality comprehensively introduces and lays the foundation for further individual growth in the burgeoning field of ecospirituality. This book is not only a foundation-laying tool for educators, but also a concise, thorough way for students and other individuals to gain a comprehensive understanding of ecospirituality and why it matters.